Integration of whole genome resequencing and transcriptome sequencing to identify candidate genes for tall and short traits in Baicheng Fatty chickens - Li, Jiaqi; Chen, Kaixu; Zhu, Mengting; Bi, Jingdong; Tang, Honggang; Gao, Weiyi (Frontiers in Veterinary Science, 2025)
The tall and short traits of chickens are significant indicators for evaluating their growth and development. Tall chickens have longer growth cycles, allowing them to accumulate sufficient nutrients and resulting in superior meat quality. This study aims to investigate the tall and short traits of Baicheng Fatty chickens and to identify relevant candidate genes. A total of 25 Baicheng Fatty chickens were selected for this research, where whole genome resequencing was performed on all samples to uncover genetic variations influencing tall and short traits. Additionally, transcriptome sequencing was conducted on 15 of these chickens to identify important genes affecting these traits through combined analysis. Using methods such as population genetic structure analysis, principal component analysis (PCA), linkage disequilibrium analysis (LD), runs of homozygosity (ROH) analysis, as well as genetic differentiation index (FST) and nucleotide diversity (θπ), a total of 1,019 candidate genes were identified through whole genome resequencing analysis. Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analyses were performed on these candidates. From the transcriptome data, 253 differentially expressed genes (DEGs) were identified, including 229 upregulated and 24 downregulated genes. GO and KEGG enrichment analyses were conducted on these differential genes, and a protein–protein interaction network for the DEGs was constructed. Through the combined analysis of whole genome resequencing and transcriptome data, six intersecting genes were identified: KLF15, NRXN1, LOC107050638, MHCY11, HAO1, and BORCS6. KEGG enrichment analysis revealed significant involvement in the Glyoxylate and Dicarboxylate Metabolism pathway, Peroxisome pathway, Carbon Metabolism, and Cell Adhesion Molecules (CAMs) pathway. These genes may influence the growth and developmental patterns of skeletal structures, though their regulatory mechanisms require further investigation. This study provides new insights for further research into the genetic mechanisms underlying chicken skeletal development and growth, as well as potential molecular markers for poultry breeding.